The Study of the Offer Forming Sources at the Cattle Meat in Gorj County - Eugenie Grigoroiu; Genoveva Buzamăt; Grigore Grigoroiu; Eugeniu Grigoroiu (Scientific Papers Animal Science and Biotechnologies, 2023)
For this study were used the basic methods of methods of investigation: the analyze, the synthesis and comparison in time and space using the typical economic indicators. The paper presents the grouping of county’s localities depending on the animals number bred at 1000 inhabitants, the grouping of the localities according to the animal number per 100 ha, the grouping of the localities according to the meat product achieved per inhabitant annually, the grouping of the localities according to the meat product achieved per ha annually.